2006
DOI: 10.1007/s00380-006-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of myocardial interstitial edema in conduction disturbances in acute myocarditis

Abstract: The presence of myocardial interstitial edema in acute myocarditis (AM) leads to thickening of the ventricular wall, and conduction disturbances, such as complete atrioventricular block (CAV), also frequently develop. This study was undertaken in order to clarify the relationship between conduction disturbances and myocardial interstitial edema in AM. The subjects comprised 50 patients with acute lymphocytic myocarditis. Based on the results of echocardiographic examinations during the acute stage, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 18 publications
1
45
0
3
Order By: Relevance
“…With respect to myocarditis, however, typically echocardiography findings do not allow for diagnosing myocarditis. 5 The scant published evidence for echocardiography findings in myocarditis includes increased wall thickness and hyperechogenicity, often accompanied by conduction abnormalities 6 ; yet, both are not frequently observed in clinical routine. This may be, in part, related to technical factors (such as the acoustic window) and physician-related factors (experience, low index of suspicion).…”
Section: Echocardiographymentioning
confidence: 99%
“…With respect to myocarditis, however, typically echocardiography findings do not allow for diagnosing myocarditis. 5 The scant published evidence for echocardiography findings in myocarditis includes increased wall thickness and hyperechogenicity, often accompanied by conduction abnormalities 6 ; yet, both are not frequently observed in clinical routine. This may be, in part, related to technical factors (such as the acoustic window) and physician-related factors (experience, low index of suspicion).…”
Section: Echocardiographymentioning
confidence: 99%
“…However, their patient had fulminant myocarditis, persistent complete AV block and a recurrence of myocarditis. Previous studies on the clinical and experimental histopathology of myocarditis suggest that myocardial interstitial edema and neural tissue damage are implicated in the transient conduction disturbances of acute myocarditis (20,21). This suggests that transient complete AV block occurring in patients with acute myocarditis, as in our case, can develop even in the absence of severe myocarditis and has the potential to cause direct damage to the AV conduction system.…”
Section: Discussionmentioning
confidence: 61%
“…Histopathological studies in previous cases suggested that myocardial edema is mainly responsible for the transient complete AV block in acute myocarditis (14). Although transient complete AV block was often seen in patients with acute myocarditis in previous reports, persistent AV block occurs in only 22-28% of patients with acute myocarditis with complete AV block (15,16).…”
Section: Discussionmentioning
confidence: 98%